Preparation, characterization and optimization of carbamazepine based pellets prepared by extrusion-spheronization technique - Makoni, Kudzai Gabriella (Rhodes University, Faculty of Pharmacy, Pharmacy)
Carbamazepine (CBZ) is an oral antiepileptic drug (AED) that is prescribed as a first-line treatment for partial seizures. CBZ is a class II compound according to the Biopharmaceutical Classification System (BCS), hence it exhibits low aqueous solubility and high gastrointestinal tract (GIT) permeability...
Keywords: Carbamazepine; Pharmacokinetics; Anticonvulsants; Drugs -- Controlled release; Drugs -- Dosage forms; Tablets (Medicine); Drugs -- Administration; High performance liquid chromatography; International Conference on Harmonisation; Experimental design